URDU TRANSLATION & VALIDATION OF COV19-IMPACT ON QUALITY OF LIFE AMONG PAKISTANI POPULATION - Riasat, Ammarah; Zaman, Noshi Iram (Pakistan Journal of Psychology, 2024)
The aim of the study was to translate, adapt and assess the psychometric properties of COV1-Impact on Quality of Life (COV19-QoL) scale in the Urdu language. In the first part of the study the English version of the scale was translated and adapted to Urdu language. Urdu translated scale was then administered on 462 individuals with the mean age of 33.57 ( SD=12.64) to assess the item correlation, validity and chronbach’s alpha of the scale. In the second part of the study, 62 participants with mean age 25.78 (SD=5.4) were included for test-retest and the linguistic eqvivalence of the translated scale. The result of Kaiser-Guttman’s and Cattell’s scree plot suggests that only one principal component emerged with a minimum 0.55 factor loading. Item total correlation ranged from .75 to .84. Cronbach’s alpha was .88 whereas test retest reliability was .85. Convergent validity was .78 and discriminant validity was -.31, and linguistic equivalence for both scales was .87. The psychometric properties of the Urdu version of COV19-QoL scale are robust enough to evaluate quality of life during the pandemic among the Pakistani community.